PENGARUH PIJAT OKSITOKSIN TERHADAP PRODUKSI ASI DI BIDAN PRAKTEK MANDIRI (BPM) R. MANURUNG KOTA PEMATANG SIANTAR TAHUN 2018 - Marlina Lamawati Simbolon (LP2MTBM MAKARIOZ, 2019)
Background: Based on the results of research conducted by Umarsari (2017) breast milk comes out from the first day (<24 hours) after giving birth. This shows the suitability of the results of the study with the theory. If no oxytocin massage is carried out, the ASI release is delayed compared to the mother who has oxytocin massage. Mothers who are not treated with oxytocin experience delayed milk removal, this can occur because the mother's nipples are very small because it will make the production of the hormone oxytocin and the hormone prolactin will continue to decline and the milk will stop. Besides the production of breast milk is strongly influenced by psychiatric factors, mothers who are always in a state of stress, sadness, lack of confidence and various forms of emotional tension will reduce the volume of breast milk will not even occur milk production. Breast milk can be produced well if the mother is calm and comfortable. Objective: This study was to determine the effect of Oxytocin Massage on increased breast milk production in the Independent Practice Midwife R. Manurung Kota Pematangsiantar in 2018. Method: The type of research conducted was quantitative research with Quasi experiment with the research design design used was post test only with design group that is, the method used in this design is that there are two groups randomly selected, then one group is given treatment, while the other is not treated and then immediately observed or measured. Results: the majority in the intervention group had enough milk production, namely 23 respondents (44.2%) mothers and in the control group 14 respondents (26.9%) had less ASI production in the intervention group, namely 3 respondents (5.76%) and in the control group 12 (23%) respondents. Conclusion: The statistical test results of the effect of oxytocin massage on breast milk production in the intervention group and the control group showed that p (sig) was 0.006 <0.05, then breast milk could be produced by concluding the effect of oxytocin massage on breast milk production in postpartum mothers in independent practice midwives R Manurung in 2018.